Assessing the legal frameworks for the protection of Internally Displaced Persons (IDPs) in the North-Eastern Nigeria - Magaji, Tasiu; Ahmad, Mohammad Zaki; Ahmad Apandi, Laila Suriya (2018)
Force displacement is a daunting challenge facing the international community as a result of armed conflicts, insurgency and communal tension. In the same vein, Nigeria has been experiencing the problem of internal displacement as a result of the Boko Haram insurgency. More than two million Nigerians have been internally displaced as a result of Boko Haram insurgency that has been bedeviling the country since 2009. Internally displaced persons differ from refugees, though they have similar characteristics. The sources of displacement of refugees and IDPs may be the same and requires equal treatment. However, IDPs have been excluded under the protection of international refugee law. This is because IDPs do not cross international borders and therefore they should be under the protection of their national governments. Sometimes the national authorities are behind the reasons for their displacement or unable to protect them. This is one of the reasons IDPs have been experiencing neglect and inadequate protection. Accordingly, Nigerian IDPs have not been adequately protected, as there is no national or international legal frameworks that are directly addressed the plight of Nigerian IDPs. Therefore, the aim of this paper is to critically assess the efficacy of the domestic and international legal frameworks on internal displacement in Nigeria. The study has adopted the use of secondary data extracted from the journals, articles, books, magazines, newspapers and reports. It employs descriptive method of data analysis. The finding is that Nigerian policy on IDPs is not effective as it has not been domesticated or implemented.